1925 Or. Gen. and Special Laws 172-73, ch. 117, § 1. - (:unkn) unknown (My University, 1925)
It shall be unlawful for any person over the age of twelve years, with or without malice, purposely to point or aim any pistol, gun, revolver or other firearm, within range of said firearm, either loaded or empty, at or toward any other person, except in self defense; and any person so offending shall be guilty of a misdemeanor and, upon conviction, shall be fined in any sum not less than $10 nor more than $500
Keywords: BRANDISHING